Potensi Bahan Pangan Lokal Indonesia Sebagai Pangan Fungsional Dan Manfaatnya Bagi Kesehatan :Review - Nathasa Weisdania Sihite; Mina Sonita Hutasoit (Poltekkes Kemenkes Semarang, 2023)
Background: Indonesia is a country known for its abundant natural resources. Recently, since the problem of the Covid-19 pandemic that has occurred in the world, functional food has begun to be studied and utilized in the health sector Functional food is a food or food ingredient that has a good function for public health in addition to the basic nutritional functions in the food. Local food ingredients in Indonesia have great potential that can be utilized to become functional food that will have a good effect on world health. Purpose: This article review aims to serve as a forum for information that discusses and analyzes the role and benefits of Indonesian functional food ingredients for health. Research Methods: The method used by a review of the literature from various scientific sources from several scientific journal articles related to functional food. Results: Functional food has an impactful role in the health sector associated with its bioactive components that are beneficial to health such as antihypertensive, antioxidant, and anti-anemia, which is why functional food was used in various industrial and health fields such as food products, food supplements, and medicine. Conclusion: The potential of available food is very beneficial for health in terms of its physiological function. Hopefully, this study on the role of functional food in the world of health can become a means and information to improve the level of public health, especially in Indonesia.